PENINGKATAN KESEJAHTERAAN WARGA KARANG TENGAH MELALUI PEMANFAATAN BUAH BERENUK MENJADI MINUMAN HERBAL - Rohaya, Nizla; Rosyidin, Ali; Mutiara, Upik (Community Services and Social Work Bulletin, 2021)
The increase in the prestige of berenuk drinks was not matched by the amount of production that was unable to meet the increasing market demand. This is because the processing is still manual and uses a very traditional method (using limited human resources), so it takes up to 12 hours to process. This is where the PKM Team of Universitas Muhammadiyah Tangerang is here to provide solutions for the two partners, where the solution will not be realized without a grant from the National Research and Innovation Agency of the Ministry of Education and Culture. The involvement of students and the contributions of the two partners during the PKM activity really helped the PKM Team of Universitas Muhammadiyah Tangerang complete the mandate from the National Research and Innovation Agency grant of the Ministry of Education and Culture completely, although it is recognized that 2 (two) components are still in the process of completion, for example: patent registration and publication of accredited journals. However, in general/overall, with all the challenges faced during the COVID-19 pandemic, the PKM Team of Universitas Muhammadiyah Tangerang has succeeded in carrying out the duties and mandates of the National Research and Innovation Agency of the Ministry of Education and Culture.